Correction: Risk factors associated with prolonged hospital length-of-stay: 18-year retrospective study of hospitalizations in a tertiary healthcare center in Mexico. - PLOS ONE Staff (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0207203.].